Concurrent or sequential use of cytotoxic chemotherapy and hormone treatment in advanced breast cancer: report of the Swiss Group for Clinical Cancer Research. Issue 6358 (1st January 1983) - Cavalli, F; Beer, M; Martz, G; Jungi, W F; Alberto, P; Obrecht, J P; Mermillod, B; Brunner, K W
Abstract : In a trial of combined hormone treatment and cytotoxic chemotherapy 464 patients with advanced breast cancer were randomly allocated to either concurrent or sequential treatment. Cytotoxic drugs were given only if the antitumour activity of the hormone treatment was inadequate. Hormone treatment consisted of oophorectomy for premenopausal and tamoxifen administration for postmenopausal patients. Length of survival was better, though not significantly, in premenopausal patients (p = 0.29) treated concurrently and in postmenopausal women (p = 0.17) treated sequentially; the difference was highly significant (p = 0.003) only for postmenopausal women in the low-risk category. The findings suggest that postmenopausal women with metastatic breast cancer should probably be treated primarily by carefully monitored hormone treatment.